Pediatricians' Attitude in Management of Acute Bronchiolitis: Did Guidelines Overcome Practices? - ÖZTÜRK, MAKBULE NİLÜFER (MARY ANN LIEBERT, INC, 2020)
Background:Acute bronchiolitis is one of the most common diseases of early childhood. There are many recent changes in the treatment of acute bronchiolitis. The aim of this study is to evaluate treatment approaches to acute bronchiolitis among clinicians and to observe compliance with clinical guidelines. Materials and Methods:Our study was designed as a multicenter cross-sectional descriptive study. A cohort of pediatric residents, fellows, and attendants were surveyed with a questionnaire including general and occupational characteristics of pediatricians and treatment choices in acute bronchiolitis. Results:A total of 713 questionnaires were collected. Most commonly applied treatment among pediatricians was inhaled salbutamol, followed by intravenous hydration, hypertonic saline, and inhaled steroid. Most commonly preferred treatment in the management of mild bronchiolitis was oral hydration and inhaled salbutamol in severe bronchiolitis. Conclusion:Although recent guidelines for the treatment of acute bronchiolitis does not support the use of many different therapies, pediatricians still tend to use them, especially bronchodilators, corticosteroids, and antibiotics.
Keywords: bronchiolitis; treatment; infant; children; guideline; CHILDREN; IMPLEMENTATION; DIAGNOSIS; INFANTS; IMPACT